1993
DOI: 10.1200/jco.1993.11.10.1919
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of combined induction chemotherapy and radiotherapy in advanced nasopharyngeal carcinoma.

Abstract: The results of this prospective study demonstrate that 5-FU plus cisplatin followed by radiotherapy can induce a durable remission in a high proportion of patients with poor-prognosis stage IV nasopharyngeal carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(33 citation statements)
references
References 34 publications
3
29
1
Order By: Relevance
“…Several Phase II trials of sequential chemoradiotherapy using induction chemotherapy for patients with NPC have demonstrated high response rates and suggested improvements in survival. [13][14][15][16] However, randomized Phase III trials have failed to demonstrate any survival benefit associated with the addition of induction chemotherapy to radiotherapy in patients with advanced-stage NPC. [17][18][19][20] One of these randomized Phase III trials was organized by the Asia-Oceania Clinical Oncology Association (AOCOA).…”
mentioning
confidence: 99%
“…Several Phase II trials of sequential chemoradiotherapy using induction chemotherapy for patients with NPC have demonstrated high response rates and suggested improvements in survival. [13][14][15][16] However, randomized Phase III trials have failed to demonstrate any survival benefit associated with the addition of induction chemotherapy to radiotherapy in patients with advanced-stage NPC. [17][18][19][20] One of these randomized Phase III trials was organized by the Asia-Oceania Clinical Oncology Association (AOCOA).…”
mentioning
confidence: 99%
“…Complete response and overall response rates reported with neoadjuvant cisplatin-containing chemotherapy were between 14% to 66% and 53% to 100%, respectively. [24][25][26][27] Among the controlled studies, only one testing neoadjuvant chemotherapy has reported its preliminary results, showing a significant difference in disease-free survival in favor of the chemotherapy arm. 28 Metastatic UCNT disease is well known for its chemosensitivity, and cisplatin-containing regimens are the most active in this disease.…”
Section: Discussionmentioning
confidence: 98%
“…In recent years, several reports in children and adults by using a combined therapeutic strategy seem to support this statement. 3,[5][6][7][8][9][17][18][19][20][21] There is a small reported evidence of NPC in children. However, therapy strategies with a combined modality showed that very good long term disease free survival might be obtained.…”
Section: Discussionmentioning
confidence: 99%
“…But in recent years, chemotherapy combined with radiotherapy has been yielding better results, with significant disease free survival improvement in children and young adults in whom the undifferentiated variant is predominant. 3,[5][6][7][8][9] The purpose of this report was to analyze features at onset, treatment results, and outcome of children and adolescents with NPC followed in our hospital since 1988.…”
Section: Discussionmentioning
confidence: 99%